PENGARUH SUBSIDI HARGA PUPUK DAN HARGA JUAL KOMODITI TERHADAP PENDAPATAN PETANI DI JORONG KUOK III KOTO NAGARI MATUA MUDIAK - Febri Sasa Milla; Khadijah Nurani (CV. Adiba Aisha Amira, 2024)
The background to writing this thesis is that there are problems among farmers such as the high price of fertilizer while the selling price of farmers' crops is uncertain. This research aims to find out whether fertilizer price subsidies and commodity selling prices have an effect on farmers' income. This research is a quantitative research using SPSS 25 software, with two types of data sources, namely primary data and secondary data using a questionnaire method after the data is collected, with 81 respondents as a sample, then the data is tested using validity, reliability, multiple linear regression tests. . The data collection technique uses a questionnaire and the analysis method used is multiple linear regression with the variables in this research, namely fertilizer price subsidies (X1), commodity selling prices (X2), and farmer income (Y). The results of the research show that the regression equation obtained is Y = 22.370 - 0.040 X1 - 0.224 . Based on the results of the t test, the significant value for the influence of 0.05 and the calculated t value is -2.121 < t table 1.990 so that H2 is accepted which means there is a negative influence of X2 on Y. The results of the F test are declared significant for the simultaneous influence of X1 and 2,839 < F table 3.11, meaning that the variable fertilizer price subsidies and commodity selling prices do not have a significant effect on farmer income. The coefficient of determination value of 6.8% is influenced by fertilizer price subsidies and commodity selling prices, while the remaining 93.2% is influenced by other variables.